Kajian Electronic Structure pada ZnO Nanoparticles Menggunakan Ionization Energy-Tight Binding Model - Yuda Prima Hardianto; Ahmad Taufiq; Arif Hidayat; Sunaryono Sunaryono; H N Ulya (JPSE (Journal of Physical Science and Engineering), 2018)
Zinc oxide (ZnO) nanoparticles have been investigated intensively related to their applications such as in optical band gap energy for semiconductor application. In general, the characterization of band gap energy of the ZnO nanoparticles has been carried out using UV-Vis spectroscopy. In this work, ionization energy-tight binding model was developed to analyze the optical binding energy of the ZnO nanoparticles. The primary technique of the electronic structure calculation was an analytical calculation of overlap integral of 2p orbital from O and 3d orbital from Zn. The result of the calculation presents that the maximum bandgap energy of ZnO particles is about of 4.4 eV. This result is almost similar to band gap energy of the ZnO nanoparticles showing by experimental result. DOI: http://dx.doi.org/10.17977/um024v3i22018p038